A General History of Japanese Cooperative Finance Thoughts (1900-2020): An Historical Approach on Cooperative Finance Thoughts in Japan - Hasegawa, Tsutomu (Journal of Development and Administrative Studies, 2025)
The mutual aid finance discussed in this paper does not necessarily deal only with literalized thoughts, nor does it deal only with that which has had a significant impact on society. The thoughts behind the behavior and conduct of the people and the operational rules of organizations may be explored from passed-down oral or written sources. In such cases, one may find some thoughts that are not logical or contradictory, or even misperceptions by today’s standards. In particular, the mindset or spirit of mutual assistance, self-reliance, and cooperation are often regarded as a spontaneous, people-led movement rather than something that emerged from policies and systems - policy plays more of a follow-up and supporting role for formalization. Therefore, the author decided to discuss the transitions of the popular thought of cooperation in financial services through the container of the organization. This kind of historical study is unprecedented, and the author believes that it can make a certain contribution to the thought of cooperative finance. The container of the organization referred to in this paper primarily refers to prewar industrial associations and credit unions, postwar credit associations, credit unions, agricultural cooperatives, and labor banks. The so-called “mujinko,” mutual financing association formed by the people is considered as prehistory in this paper.